Phenophysiological variation of a bee that regulates hive humidity, but not hive temperature. - Ayton, S.; Tomlinson, S.; Phillips, R.; Dixon, Kingsley; Withers, P. (2016)
Seasonal acclimatisation of thermal tolerance, evaporative water loss and metabolic rate, along with regulation of the hive environment, are key ways whereby hive-based social insects mediate climatic challenges throughout the year, but the relative importance of these traits remains poorly understood. We examined seasonal variation in metabolic rate and evaporative water loss of worker bees, and seasonal variation of hive temperature and humidity, for the stingless bee Austroplebeia essingtoni (Apidae; Meliponini) in arid tropical Australia. Both water loss and metabolic rate were lower in the cooler, dry winter than in the hot, wet summer at most ambient temperatures between 20°C and 45°C. Contrary to expectation, thermal tolerance thresholds were higher in the winter than in the summer. Hives were cooler in the cooler, dry winter than in the hot, wet summer, linked to an apparent lack of hive thermoregulation. The humidity of hives was regulated at approximately 65% RH in both seasons, which is higher than unoccupied control hives in the dry season, but less than unoccupied control hives in the wet season. While adaptations to promote water balance appear more important for survival of A. essingtoni than traits related to temperature regulation, their capacity for water conservation is coincident with increased thermal tolerance. For these small, eusocial stingless bees in the arid tropics, where air temperatures are relatively high and stable compared with temperate areas, regulation of hive humidity appears to be of more importance than temperature in maintaining hive health.